2011
DOI: 10.1007/s11433-010-4231-7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and optical properties of Sn2x Ga2(1−x)O3 compounds

Abstract: Band structure, density of states, electron density difference, and optical properties of intrinsic -Ga 2 O 3 and Sn 2x Ga 2(1x) O 3 (x= 3.125%-6.25%) compounds are studied using first-principle calculations based on the density functional theory. The anisotropic optical properties are investigated by means of the complex dielectric function, which are explained by the selection rule of band-to-band transitions. All the calculation results indicate that the conductivity of Sn 2x Ga 2(1x) O 3 is super to -G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…It is obvious that all the distributions are different: they peak respectively at 2𝑐. A recent empirical research [21] has indicated that most of urban human individuals have peaked travel distance distributions, peaking at the distance between his or her two most visited locations, coinciding with our model results. These results suggest that although the empirical evidence in Ref.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…It is obvious that all the distributions are different: they peak respectively at 2𝑐. A recent empirical research [21] has indicated that most of urban human individuals have peaked travel distance distributions, peaking at the distance between his or her two most visited locations, coinciding with our model results. These results suggest that although the empirical evidence in Ref.…”
supporting
confidence: 88%
“…Actually, the emergence of the heavy-tailed nature at the population level can also result from the heterogeneity of the distance between people's home and workplace. [21] Therefore, the radius of gyration may not be used as a group measure to distinguish the population-based heterogeneity from the individual scaling law of the travel distance distributions.…”
mentioning
confidence: 99%